A qualitative assessment of mothers' perceptions and behaviors in response to an intervention designed to encourage safe child feces management practices in rural Odisha, India. (19th April 2022) - Williams, Rebekah N.; Sclar, Gloria D.; Routray, Parimita; Majorin, Fiona; Blais, Linelle; Caruso, Bethany A.
Abstract: Child feces are not always safely disposed of into a latrine, potentially contributing to fecal exposure in the household environment. In India, safe disposal of child feces is a relatively uncommon practice despite gains in latrine coverage. This study took place after the delivery of a behavior change intervention that also included the provision of potties and scoops. The aims of this research were to (1) describe current child feces management (CFM) practices, (2) explore perceptions and behaviors of mothers who participated in intervention activities, and (3) assess the spillover of intervention activities in neighboring villages. Twenty-four in-depth interviews and four focus group discussions were conducted across six villages, three of which received the intervention. Using thematic analysis, we explored caregivers' descriptions of the different strategies to manage their child's feces. The study found (i) women's access to and perception of the intervention informed their knowledge, attitudes, perceived risk, and behaviors related to CFM, (ii) most women positively perceived the messages of the intervention with varying use of the tools provided for feces disposal, and (iii) there was no spillover in the neighboring villages. Our findings underscore that CFM practices must be addressed to reduce fecal contamination of the environment. HIGHLIGHTS: Family roles and responsibilities often interfered with the ability of mothers to attend the intervention. Caregivers employed a variety of fecal management strategies dependent on the age of the child and location of defecation. Participants in intervention villages reported some level of use of the child feces management tools provided in the intervention, with mixed reviews on the acceptability and usefulness of these tools.